Antioxidant activity evaluated in vitro of endophytic fungi isolated from Talinum triangulare leaves - GONO Kpan Nestor,; Pakora Gilles Alex,; Ako Aristide Berenger,; Yeo Dodehe,; N’Douba Kacou Adèle, (International Journal of Phytomedicine, 2021)
Endophytic fungi are microbes that reside in the tissues of living plants without causing any apparent damage. They are very diverse microorganisms that synthesize compounds of various classes within their host plants. The aim of this work is to evaluate the total phenol content and antioxidant capacity of endophytic fungal extracts isolated from the leaves of Talinum triangulare. For this purpose, the extraction of metabolites was carried out using ethyl acetate. The total phenols of the fungal extracts were determined by the classical colorimetric method of Folin-Ciocalteu and the antioxidant capacity was evaluated by the 1,1-diphenyl-2-picrylhydrazyl free radical scavenging method and the FRAP method. A total of four endophytic fungi coded CETt-01 to CETt-04 were isolated from this study. The CETt-02 endophyte showed higher antioxidant activity with an IC50 = 0.186 ± 0.043 mg/mL. This high antioxidant activity is positively correlated with its total phenol content. The genomic DNA of the active fungal strain (CETt-02) was isolated and ITS specific regions were amplified and sequenced. Thus, the characterization of this isolate by biology allowed to identify it as Diaporthe fraxini-angustifoliae. This work shows an interesting approach for the discovery of new natural antioxidant compounds.